Connecting virtues : advances in ethics, epistemology, and political philosophy - Croce, Michel, 1988-; Vaccarezza, Maria Silvia (Hoboken, NJ : John Wiley & Sons, 2018)
Connecting Virtues examines the significant advances within the fast-growing field of virtue theory and shows how research has contributed to the current debates in moral philosophy, epistemology, and political philosophy. -Includes groundbreaking chapters offering cutting-edge research on the topic of the virtues -Provides insights into the application of the topic of virtue, such as the role of intellectual virtues, virtuous dispositions, and the value of some neglected virtues for political philosophy -Examines the relevance of the virtues in the current debates in social epistemology, the epistemology of education, and civic education -Features work from world-leading and internationally recognized philosophers working on the virtues today.
Utrum sit una tantum vera enumeratio virtutum moralium / Sophie Grace Chappell -- Generosity : a preliminary account of a surprisingly neglected virtue / Christian B. Miller -- An eye on particulars with the end in sight : an account of Aristotelian phronesis / Maria Silvia Vaccarezza -- Honesty as a virtue / Alan T. Wilson -- Virtue epistemology, enhancement, and control / J. Adam Carter -- Epistemic paternalism and the service conception of epistemic authority / Michel Croce -- Neuromedia and the epistemology of education / Duncan Pritchard -- Epistemic vice and motivation / Alessandra Tanesini -- Senses of humor as political virtues / Phillip Deen -- Citizens' political prudence as a democratic virtue / Valeria Ottonelli -- Hope as a democratic civic virtue / Nancy E. Snow.
'First published as Metaphilosophy volume 49, no. 3 (April 2018).'
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Virtues; Knowledge, Theory of; Political science -- Philosophy; Electronic books